Developing Domain Ontology for Issuing Certificate of Citizenship of Nepal (Journal of Information Technology and Digital World, 2020)
Most of the existing software systems are web-based and interactive. Semantic Web Technologies further allows for organizing and encoding information meaningfully. It enables software agents to interpret the information. However, the representation of information in different format has made challenging to interoperate among the heterogeneous systems. The representation of heterogeneous system with common standards and vocabularies is an effective solution for interoperability. For this, development of domain ontology is required for common understanding of the concept. The research work is mainly focused on development of domain ontology for issuing Citizenship of Nepal as e-government is widely considered as a good example of heterogeneous system. Protégé is used as ontology editor and Web Ontology Language (OWL) is used for representation of the concepts. A hybrid methodology with Unified Modelling Language (UML) is used to get in-depth concept of the domain. The domain ontology is verified using built-in reasoner of Protégé and validated with answering competency questions of the domain using SPARQL query.
Keywords: Certificate of Citizenship; Domain Ontology; OWL; Protege; SPARQL; Unified Modelling Language